Object-Oriented Analysis And Design Of Research Seminar Online Registration In Higher Education - Prayughi, Pungki; Hermadi, Irman (Perpustakaan IPB, 2015)
Nowadays the quality aspects of information technology (IT) implementation plays an imperative role in the case of supporting services to its related stakeholders, mainly more on the issue of an effective and efficient process. To provide a more reliable, understandable, reusable, and maintainable academic information systems, Graduate School of IPB needs to improve the quality of its IT. Development of information systems (IS) through the proper stages of analysis and design expected to create a reliable and qualified IS. This research will evaluate the effectiveness of Academic Management IS. An evaluation conducted by observing the current system, using questionnaires, and measurement using a Likert scale. Questionnaire instrument tested for its validity (Product Moment) and reliability (Cronbach's Alpha) using SPSS version 19. This study adopts an integrated database schema that IPB has developed and designing research seminar online registration prototypes using object-oriented approach for a better IS future development.Keywords: Object-orientedapproach, prototypes, Reliability Alpha Cronbach’s, Skala Likert, SPSS, Validity Product Momen